Heterogeneous phenotype of a Chinese Familial WHIM syndrome with CXCR4V340fs gain-of-function mutation - Huang, Yu; Li, Lu; Chen, Ran; Yu, Lang; Zhao, Shunkai; Jia, Yanjun; Dou, Ying; Zhang, Zhiyong; An, Yunfei; Tang, Xuemei; Zhao, Xiaodong; Zhou, Lina (Frontiers in Immunology, 2024)
BackgroundWHIM syndrome is a rare, autosomal dominant inborn error of immunity characterized by warts, hypogammaglobulinemia, infection, and myelokathexis. It is caused mainly by heterozygous mutations at the C-terminus of the C-X-C chemokine receptor type 4 (CXCR4) gene.MethodsWe described the detailed clinical, genetic, immunological and treatment characteristic of four WHIM patients from a single Chinese family.ResultsHere, we report four patients from a family carrying a variant of CXCR4 (c.1016_1017dupCT), which introduces a frameshift at codon V340, resulting in an extension of 14 amino acids (p.V340L fs*27). We provide an in-depth analysis of their clinical, genetic, immunological and treatment characteristic, noting that these patients exhibited an atypical clinical phenotype when compared to reported CXCR4R334X patients. Additionally, the frameshift variant CXCR4V340fs led to impaired receptor downregulation in patients’ PBMCs, and in HEK293T cells transfected with the variant plasmids.ConclusionsOur study provided detailed clinical features of four CXCR4V340fs WHIM patients from one Chinese family who presented atypical phenotype and enrich the spectrum of WHIM syndrome.